KUALITAS PELAYANAN PUBLIK DAN KEPUASAN PELANGGAN - ', Yulianti (Jurnal Ilmu Administrasi Negara, 2016)
Analysis of Customer Satisfaction Based on Quality Public Services. The aim of this study was to determine the quality of public services and customer satisfaction in the claims process Old Age Security (JHT). The method used is quantitative descriptive. Sampling was done by using simple random sampling (simple random sampling). The samples used in this study amounted to 90 respondents. Statistical analyzes were used to test the hypothesis in this research is descriptive analysis and statistical analysis. The calculation process is done with the help of the program package SPSS for Windows version 17. Results showed the average value of the quality of service on each of the indicators show that the level of achievement of the quality of public services can be categorized as high. While the average score of customer expectations for quality of service is equal to 4.47 in order to obtain a score gap between perception (reality) which is perceived by customers in the hope that the customer wants unmet amounted to -0.63. This condition indicates that customer satisfaction with the services.